2009
DOI: 10.1007/s11030-009-9128-x
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective synthesis of fused [1,3]thiazolo[1,3]oxazins and [1,3]oxazino[2,3-b][1,3]benzothiazoles

Abstract: An efficient diastereoselective synthesis of 7-ethyl 5,6-dialkyl 7H-[1,3]thiazolo[2,3-b][1,3]oxazin-5,6, 7-tricarboxylates and 2-ethyl 3,4-dialkyl 2H-[1,3]oxazino [2,3-b][1,3]benzothiazole-2,3,4-tricarboxylates via reaction of thiazole and benzothiazole with dialkyl acetylenedicarboxylates in the presence of ethyl pyruvate is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…[ It should be noted that isatins bearing 1-benzyl and 1-n-butyl groups gave relatively higher yields than those of other isatins due to the better solubility of the zwitterionic salts. The structures of prepared zwitterionic salts 2a-n were fully confirmed by 1 H NMR, 13 C NMR, and IR spectroscopy and HRMS and were further confirmed by single-crystal X-ray diffraction studies performed for compound 2e (Figure 1). The structures of prepared zwitterionic salts 2a-n were fully confirmed by 1 H NMR, 13 C NMR, and IR spectroscopy and HRMS and were further confirmed by single-crystal X-ray diffraction studies performed for compound 2e (Figure 1).…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…[ It should be noted that isatins bearing 1-benzyl and 1-n-butyl groups gave relatively higher yields than those of other isatins due to the better solubility of the zwitterionic salts. The structures of prepared zwitterionic salts 2a-n were fully confirmed by 1 H NMR, 13 C NMR, and IR spectroscopy and HRMS and were further confirmed by single-crystal X-ray diffraction studies performed for compound 2e (Figure 1). The structures of prepared zwitterionic salts 2a-n were fully confirmed by 1 H NMR, 13 C NMR, and IR spectroscopy and HRMS and were further confirmed by single-crystal X-ray diffraction studies performed for compound 2e (Figure 1).…”
Section: Resultsmentioning
confidence: 63%
“…[1][2][3][4][5][6] Five-membered heterocyclic ammonium salts such as imidazolium salts have also attracted much attention [7][8][9] aside from their use as ionic liquids and precursors of N-heterocyclic carbenes. [10][11][12][13] Recently, we found that the one-pot reactions of N-benzylbenzimidazolium salts, aromatic aldehydes, and active methylene compounds gave a series of zwitterionic salts or functionalized pyrrolo[1,2-a]benzimidazoles in good yields. [10][11][12][13] Recently, we found that the one-pot reactions of N-benzylbenzimidazolium salts, aromatic aldehydes, and active methylene compounds gave a series of zwitterionic salts or functionalized pyrrolo[1,2-a]benzimidazoles in good yields.…”
Section: Introductionmentioning
confidence: 99%
“…The 13 C NMR spectrum of 4a showed 20 distinct resonances in agreement with the proposed structure. In addition, product 4a displayed 13 C NMR resonances at δ = 50.25, 66.52, 68.19 and 88.71 ppm, respectively, for the O═C– C –C═O, N‐CH‐ C H‐CO 2 Me, N‐ C H‐CH‐CO 2 Me and S‐ C ‐N units . In the 13 C NMR spectrum, the five carbonyl groups were seen at δ = 150.99, 165.39, 167.81, 169.82, and 171.62 for the 2C═O amid and 2C═O ester.…”
Section: Resultsmentioning
confidence: 99%
“…The residue was recrystallised from 2:1 n-hexane/EtOAc. 3.79 (3H, s, OMe), 6.63 (1H, s, N-C=CH-CO 2 Me), 6.63-7.97 (4H aro ). 13 …”
Section: General Proceduresmentioning
confidence: 99%
“…1,2 Some heterocyclic compounds containing a thiazole ring in their structures have important applications in pharmaceutical as well as in agrochemical chemistry. [3][4][5] Compounds with benzothiazole skeletons are of paramount interest because of their antitumour, anticancer, and antibacterial activities. [6][7][8][9][10] In addition, the benzothiazole nucleus is a key element in some thermally stable rigid-rod polymers, possessing high tensile strength and modulus.…”
mentioning
confidence: 99%